Development of High Performance (Mechanical and Wear Properties) of AA 6061-Hybrid Nano Composites Via Liquid Metallurgy Route - Al-Alkawi, Hussain J. M.; Hanfesh, Abduljabbar Owaid; Rauof, Saja Mohammed Noori Mohammed (Al-Nahrain Journal for Engineering Sciences, 2019)
This research is devoted to study the influence of different weight percent concerning to the additions of Ti and Cu on mechanical and tribological properties of AA6061. The composite materials consist of different weight percentage of Ti (0.2, 0.4, and 0.6) wt% and constant weight percentage of Cu (0.2) wt% which were fabricated by liquid metallurgy route technique. Microstructural characterization and phases have been examined by using SEM (scanning electron microscopic).SEM examination showed uniform distribution of nano Ti and Cu in AA6061. The consequences of mechanical tests demonstrated clear enhancement in mechanical properties, such as ultimate tensile strength, yield strength, young modulus, ductility% and hardness at additive percentage of 0.4% Ti+0.2%Cu nano particles incorporated into molten AA6061. Percentage of enhancement ultimate tensile strength is about 73.3%, yield strength about 82.7%, young modulus is about 21.2%, the  Vickers hardness about 42.6% and the decreasing in ductility was about 25.2% compared with the metal matrix (AA6061). The wear rate test was performed by using pin on disc rig for both hybrid nano composite and base metal (AA6061) under various loads (10,15and 20) N with sliding speed (1.282) m/sec at a (10) min’s time. The results showed a decrease in wear rate at 0.4%Ti+0.2%Cu compared with the base metal (AA6061). Improvement percentage of wear rate is about 105% at 20 N load.